A construção discursiva do sistema de cotas na revista "Caros Amigos" - Freitas, Irene de Lima (2011)
This research aims at discussing how the construction of the discourse concerning quotas in Brazil happens in the media, and how it is fits into the debate about exclusion/inclusion of the Negroes in the Brazilian society. Due to the vastness of the issue, the object of the study was chosen, taking into consideration, firstly, the year 2002, the period of most commotion in the media, relating to the discursive impact of exclusion, having as the background the issue of the quotas. During this year, a publication that systematically wrote about the subject was the magazine Caros Amigos. Thus, considering that the Legislative Assembly of the State of Rio de Janeiro instituted quotas of up to 40% for the access of the Negro and dark population to the Federal University of the State of Rio de Janeiro, based on Law number 3,708, dated 9 November 2011, the magazine was the one chosen to be analyzed, as from the editions published in the months of June to November 2002. Before the analysis in itself, and in order to fundament it historically, we searched for information about the antecedents of this policy called affirmative action aiming at understanding which elements helped to bring about the fact of such measures being taken up in Brazil. Secondly, we chose, in the total of editions selected, 5 articles, 6 letters from readers and 6 magazine covers, all dealing with the matter of quotas and we considered each one of them as verbal and/or verbo-visual utterances. We understand utterances as discursive practices that enable the study and understanding of their functioning as from the crisscrossing of the materiality of the language present in them, as well as the conditions of production, circulation and reception that serve as background. The basic theoretical and methodological perspective is the dialogical theory/analysis of discourse, as put forward in the works of M. Bakhtin and his Circle, especially in that it refers to the notions of verbal interaction, utterance and forms of presence in the discourse of the other. The social relevance of this research is due to the importance that the policy concerning quotas took on in the Brazilian society and also due to the fact that it explores the issue in a dialogic perspective, in other words, understanding interaction as the founding principle of language which articulates in specific historical, social and cultural contexts. It is also relevant to investigate verbal and verbo-visual texts/discourses considering a culture magazine, in this case, Caros Amigos. As a result of the study, it may be stated that the multiple voices and senses present in the texts that make up the corpus - magazine covers, articles, letters from readers - show that the magazine builds up its editorial positioning before the object of discourse, as from the value that interlocutors attribute to its construction; the polemic is part of the magazine editorial line of thought; the opposition between interlocutors determines the construction of the statements; while opening up space for discussions concerning different visions of the world, it contributes to social transformation; the dialogic analysis of the statements in the media contribute to a better understanding of the social nature of discourse as well as the subjects which are relevant to society, like the quota issue